Euro Area Policies : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report, 2010)
The EU crisis was caused by unsustainable policies in some member countries, and has put the spotlight on the deficiency of area-wide mechanisms in disciplining fiscal and structural policies. Despite a strong and far-reaching policy response, market confidence will take time to restore. Fiscal sustainability needs to be established. Growth needs to be boosted through swift implementation of structural reforms. The resilience of the banking system must be improved and its stability assured. Progress in building the EU's financial stability architecture should be pursued.